Deskripsi Kemampuan Berpikir Kritis Siswa SMA melalui Model Pembelajaran CLIS (Children Learning In Science) Berbantuan LKS pada Materi Elastisitas dan Hukum Hooke - Metta Kisti Dewi Renjani; Susilawati Susilawati; Nur Khoiri (Universitas PGRI Semarang, 2018)
The aims of this study is to determine the improvement of students' critical thinking skills based on the application of CLIS method (Children Learning In Science) LKS assisted on elasticity and Hooke Law in SMA Negeri 1 Jakenan Pati. This research was conducted at SMA N 1 Jakenan Pati dated October 13 until October 24, 2017. This research used Quasi Experimental design in the form of pretest-posttest control group design. Population in this research is all class XI IPA in SMA Negeri 1 Jakenan Pati, while sample of research used consist of two classes taken by cluster random sampling technique so that obtained class XI IPA 8 which amounted to 40 students as experiment class using CLIS method (Children Learning In Science) assisted by LKS, and XI IPA 7, amounting to 40 students as control class using Direct Instruction learning model. Based on the result of the research obtained the mean of pretest experimental class is 55,2 and control class 49,45, while value of experimental class postest 79,1 and control class 68,7. The hypothesis testing shows that with t test s2 polled variance magnitude thitung = 19.5 and ttabel = 1.66. This indicates thitung > ttabel, so Ho is rejected which means there is increasing in the effectiveness of CLIS learning method (Children Learning In Science) assisted by LKS on students' critical thinking ability.